A COMPARATIVE STUDY OF SPORTS COMPETITION ANXIETY LEVEL BETWEEN HOST PLAYERS AND VISITORS PLAYERS DURING THE 3RD EDITION OF KHELO INDIA WINTER GAMES - Choudhary, Sneha; Ahmad Malik, Shabir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to compare sports competition anxiety level between host players and visitor players those who have participated in the third edition of khelo India Winter Games at Gulmarg. For the investigation of the study, total 80 players were selected by using simple random sampling technique among them 40 were host players who reside in Jammu & Kashmir while as 40 visitor players who came from outside Jammu and Kashmir were selected as participants. To achieve the purpose of the study, Sports Competition Anxiety Level test developed by Martens 1990 was used. For data analysis descriptive statistics i.e Mean, Frequency percentage, S.D and inferential statistics t-test was applied. Results shows that there is significant difference between host and visitor players in respect to sports competition anxiety level. Further findings of the study shows that visitor players have high level of sports Competition anxiety level as compare to host players.